Prevalence of Thrombocytosis in Children with Iron Deficiency Anemia - Khan, Naseemullah; Shahzad, Qamar Uz Zaman; Ramzan, Atiqa; Ali, Ayesha; Fatima, Kanwal; Ejaz , Feeza (Indus Journal of Bioscience Research, 2025)
Background: Iron deficiency anemia (IDA) is the most common nutritional deficiency in children and is often associated with hematological abnormalities beyond anemia itself, including reactive thrombocytosis. Objective: To determine the prevalence of thrombocytosis among children diagnosed with iron deficiency anemia and to analyze its association with demographic and clinical variables. Methods: This cross-sectional study was conducted at the Department of Pediatric Medicine, Shalamar Hospital, Lahore, over a defined period. A total of 200 children aged 1 to 12 years with diagnosed IDA were enrolled through non-probability consecutive sampling. Demographic and clinical data were collected using a structured proforma. Blood samples were analyzed for hemoglobin, serum ferritin, and platelet count. Results: The mean age of participants was 6.4 ± 3.1 years, and 54% were male. Thrombocytosis was found in 138 out of 200 children (69%). It was more common in children with serum ferritin